Vpliv pospešenega staranja na mehanske lastnosti plošč iz mineralnih vlaken - Ducman, Vilma (Kovine zlitine tehnologije, 1998)
The aim of the experiments described in the contribution was to determine the resistance of mineral-wool boards to weathering. It has been frequently observed that the mechanical properties of such boards worsen after they have been stored and/or exposed to weathering for longer periods of time. In the experiments, mineral-wool boards were subjected to accelerated ageing in a climatic chamber, at temperatures ranging from -20oC to +50oC, and under different conditions of relative humidity. The compressive strength and tensile strength of the tested samples were measured on aged and non-aged boards. It was found that the compressive strength of the aged boards was reduced by up to approximately 20% in comparison with that of non-aged boards,whereas tensile strength was reduced by to 70%.
Keywords: mehanske lastnosti; mineralna vlakna; staranje; plošče